THE PROGRESS OF ISLAMIC CRIMINAL LAW IN INDONESIA: AN ANALYSIS OF THE DYNAMIC AND THE URGENCY OF ITS IMPLEMENTATION - Vianne, Virginia Harizta (Sriwijaya Crimen and Legal Studies, 2023)
Although the application of Islamic criminal law still raises pros and cons due to the assumption that the sanctions tend to be sadistic. It does not mean Islamic criminal law is impossible to apply in Indonesia. Positive law in Indonesia results from thinking based on three components that substantially influence European, customary, and Islamic law. The problem related to the formation of positive law in Indonesia is the position of Islamic law, especially those still vague and unfamiliar to the public. So that the formulation of the problem in this study is: how are the dynamics of existence and the urgency of applying Islamic criminal law in Indonesia? This research used normative juridical methods or legal research. The study results show that the dynamics of Islamic criminal law in Indonesia began in the colonial period as a subsystem of customary law. As for the legalization process of Islamic law or criminal law in Indonesian law, it cannot be carried out easily due to the tendency of the influence of Western state law, which previously colonized Indonesia. Nowadys, Islamic criminal law has been applied to one of Indonesia’s regions, namely Nanggroe Aceh Darussalam. Another dynamic that Indonesia has to face in implementing Islamic criminal law is the existence of a stigma that punishment in Islamic criminal law seems sadistic and inhumane or violates human rights. The urgency of implementing Islamic criminal law in Indonesia is that Islamic criminal law contains more than all the goals commonly known in the world of criminal law, namely retribution, deterrence, and reformation.